Safety Performance in Middle Scale Industry: A Literature Review - Desak Nyoman Dewi; Fendy Suhariadi; Seger Handoyo (Universitas Ahmad Dahlan, 2020)
Safety performance is a performance concept which focuses on employeeâ€™s behavior in the context of work safety. Safety performance has been frequently studied in multiple industrial contexts. However, only a few of them aimed for middle scale industries. Previous studies on safety performance were usually conducted more on large scale industries, in which the outcome refers more on the safety performance focusing on work injury, work accident or unsafe behaviors. There are only limited numbers of studies on work behaviors, especially on middle scale industries. This research aimed to identify the opportunities and challenges on the application of safety performance in relations to the work behaviors in the middle scale industries through a library study. Literature search were conducted by online means from four databases: ProQuest e-journal, ScienceDirect e-journals, Sage e-journals, and emerald insight e-journals. The keywords used in the search were (â€œsafety performanceâ€ or â€œsafety behaviorâ€), (â€œmedium industriesâ€ or â€œsmall and medium enterpriseâ€ or â€œSMEâ€), (â€œsafety in medium industriesâ€ or â€œsafety in SMEâ€), and (â€œsafety performance in medium industriesâ€ or â€safety performance in SMEâ€). There were 33 journals found which were later mapped based on the inclusion or exclusion criteria. Results showed that the flexibility of middle scale industries, collectivistic culture and the role of leaders are the potential supporting factors in the application of safety performance in middle scale industries. On the other hand, factors such as human resources, economy, technology, the organization of middle scale industry and the government regulations are the potential inhibiting factors in the application of safety performance in middle scale industries.Keywords: safety performance, middle scale industry, work safety